KONSEP KEPEMIMPINAN ISLAM UMAR BIN KHATTAB DAN RELEFANSI DI ERA SEKARANG - Harahap, Wenni Erlis Fiani; Zunika, Rosa Er; Azmi, Agil Fadlul (Educational Leadership: Jurnal Manajemen Pendidikan, 2025)
The era of Caliph Umar bin Khattab as the most luminous story sheet of Islamic history that highlights and surpasses every story. This study aims to find out how Islamic civilization was during the era of Umar bin Khattab, how the administrative system of state financial institutions was. In order to be a reference or guideline for today's leaders. The type of this research is literature, including the type of literature review research. This research is a type of research used in collecting information and data in depth through various literature. The data sources in this study are primary data sources and secondary data sources. The primary data source is the main data reference in this study, namely the biography of Umar bin Khattab by Pro. Dr. Ali Muhammad Ash-Shallabi. While the secondary data source is a complementary reference as well as supporting data for the primary data source. Umar bin Khattab began to observe the country's wealth whose sources of income began to increase rapidly. Umar bin Khattab began to develop the country's financial system, both in terms of sources of income, spending, or the order of people who have the right to receive it in the administration system. In developing the financial institution, Umar bin Khattab tried to always apply ijtihad that was similar to the goals of Islamic law and the welfare of the people